Diabetes Related Knowledge, Attitudes and Practice – A Survey Among Oral Health Professionals in Victoria, Australia - Chinnasamy A; Moodie M (Dove Medical Press, 2020)
Alagesan Chinnasamy,1 Marjory Moodie2 1Melbourne Dental School, The University of Melbourne, Melbourne, VIC, Australia; 2Deakin Health Economics, Deakin University, Geelong, VIC, AustraliaCorrespondence: Alagesan ChinnasamyMelbourne Dental School, 720 Swanston Street, Carlton, Melbourne, VIC 3053, AustraliaTel + 61 426931940Email a.chinnasamy@student.unimelb.edu.auPurpose: Until now, little is known as to how well the evidence supporting the link between periodontal disease and diabetes is incorporated in the dental practice, in Australia. This study aims to explore Oral health Professionals (OHP) knowledge, attitudes, and practice (KAP) towards diabetes screening in the dental setting.Methods: The survey questionnaire consisted of sociodemographic, practice characteristics and Likert scaled questions categorised in different domains of KAP and one additional domain as barriers. A Mann–Whitney and Kruskal–Wallis test was performed to determine differences in the OHP response. To predict if practice behavior was influenced by knowledge and attitudes, a multiple linear regression was conducted.Results: A total of  197 respondents were included in the analysis of the results. General dentists constituted 64.6% of the response. For chairside screening of diabetes, 58% felt it was essential and 70% felt it was appropriate. More public sector OHP (79%) felt it is important to conduct chairside screening for T2DM. Patient willingness was identified as the most important and insurance coverage as the least important (43%) consideration for T2DM screening.Conclusion: Overall, knowledge, attitude and practice towards DM were positive, but a significant proportion of the OHP felt chairside screening may not be appropriate or important.Keywords: diabetes, oral health professional, screening, periodontal disease